Influence of health care practices on the burden of caregiver mothers - Fernanda Yeza Ferreira; Mariane Caldeira Xavier; Paula Rossi Baldini; Larissa Tassim Luciano Ferreira; Regina Aparecida Garcia Lima; Aline Cristiane Cavicchioli Okido
ABSTRACT Objectives: to explore the influence of health care practices on the burden of caregiver mothers of children with special health needs. Methods: observational, analytical, cross-sectional, quantitative study. Participation of 100 caregiver mothers, who responded the following instruments: characterization instrument; Burden Interview for Informal Caregivers; Perceptions of Family-Centered Care - Parents version; Evaluation Instrument for Primary Care - Child Version. For statistical analysis, were used the Spearman's Correlation and univariate and multivariate linear regression analysis. Results: the mean burden score was 47.99. There was a negative correlation between the burden and the domains of collaboration and support of the Perceptions of Family-Centered Care scale. In the multivariate linear regression model, the longitudinality variable maintained a significant relation with the burden (p = 0.023). Conclusions: a shared, longitudinal and integrated care between families and health services can ease the burden of caregiver mothers.